BERILO DOS PEGMATITOS IPÊ, FERREIRINHA, JONAS LIMA E ESCONDIDO, GOVERNADOR VALADARES, MG: DADOS CRISTALOQUÍMICOS - Carvalho, D. T. de Newman; Gandini, A. L.; Bello, R. M. S.; Fernandez, M. L. S.; Marciano, V. R. P. R. O.; da Costa, G. M.; Souza, L. A. C. (Geochimica Brasiliensis, 2012)